PENERAPAN MODE LINGUISTIK DALAM VIDEO KANAL YOUTUBE KINDERFLIX: KAJIAN SEMIOTIKA - Indriana Sulistyo Rini; I Wayan Letreng; Sri Yanuarsih (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to examine the application of the linguistic mode in educational videos on the Kinderflix YouTube channel using a social semiotic approach. The linguistic mode refers to the use of spoken language as a primary tool for delivering messages, building interaction, and shaping meaning. In the context of educational videos, the linguistic mode is applied through narration, invitations, questions, and verbal praise delivered by the narrator. This research employs a descriptive qualitative method with observation and note-taking techniques to collect data from two Kinderflix videos. The data were analyzed using Kress and van Leeuwen’s theory of multimodality and Halliday’s systemic functional linguistics. The findings show that the linguistic mode in Kinderflix videos not only conveys information explicitly but also functions as a visual guide, a cognitive stimulus, and a medium for fostering social interaction with child audiences. Verbal language works integratively with other modes such as visual, auditory, and gestural to create an interactive and educational multimodal communication experience.